2012
DOI: 10.1111/j.1548-7466.2011.01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity Lockdown: The Formation of Black Masculinity in a California Public High School

Abstract: Masculinity Lockdown is an ethnographic study that analyzes the construction of Black masculinity at Southeast County High School (SCHS) in Southern California. Specifically, the article examines how three young Black males at SCHS navigate amidst a social milieu established by the school that denies the assertion of race and simultaneously fosters a homophobic understanding of masculinity. Through ethnographic accounts, the piece details how explicit utilization of violent, sexist rhetoric encourages Black ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Because of its social justice theme, Robeson appears to be the complete inverse of the "paradigm of overt homophobic discourse and the removal of race" 16 that one might find at a typical urban California high school. This is a school where the white administrator has asked police to park down the hill instead of in the parking lot whenever they have business in the building, so as not to create a militarized environment.…”
Section: Black Queer Common Sensementioning
confidence: 99%
See 1 more Smart Citation
“…Because of its social justice theme, Robeson appears to be the complete inverse of the "paradigm of overt homophobic discourse and the removal of race" 16 that one might find at a typical urban California high school. This is a school where the white administrator has asked police to park down the hill instead of in the parking lot whenever they have business in the building, so as not to create a militarized environment.…”
Section: Black Queer Common Sensementioning
confidence: 99%
“…However, the frequency of its usage does not rinse "bitch" of its misogynoiristic valence. For more on misogynoir and the term bitch, see Antonia Randolph, "Why Bitch Isn't Nigger: Misogynoir and the False Equivalences of Hip Hop" (paper presented at the annual meeting for the National Women's Studies Association, Baltimore, MD, November [16][17][18][19]2017).…”
Section: On the Shoreline: A Portal To Black Queer Kinshipmentioning
confidence: 99%
“…In terms of hierarchy, focus group participants noted that White and Brown students were higher in the hierarchy than Black students, who were therefore subjected to differential discriminatory treatment by teachers. Previous research has demonstrated that teachers of Black males are usually White middle-class females who often draw upon the dominant discourse of Black students being deficient when interacting with them (Schnyder 2012). This finding may help explain the difficult teacher-student relationships and differential treatment reported by participants, who complained of teachers refusing to provide academic assistance when requested; surveillance of them while other students who exhibited similar or worse behaviour went unpunished or received lighter punishment; and school reports sent to their parents without the courtesy of knowing first.…”
Section: "Regular Students": Adaptive Positioning and The Constructs mentioning
confidence: 99%